Finance and Hunger : Empirical Evidence of the Agricultural Productivity Channel - Claessens, Stijn (World Bank, Washington, DC, 2012)
Using cross-country and panel regressions, the authors show that financial sector development significantly reduces undernourishment (hunger), largely through gaining farmers and others access to productivity-enhancing equipment, translating into beneficial income and general effects. They show specifically that a deeper financial sector leads to higher agricultural productivity, including higher cereal yields, through increased fertilizer and tractor use. Higher productivity in turn leads to lower undernourishment. The results are robust to various specifications and econometric tests and imply that a 1 percentage point increase in private credit to GDP reduces undernourishment by 0.22-2.45 percentage points, or about one-quarter the impact of GDP per capita.